La pauvreté en rural ; quels acteurs, quelles actions pour quels projets ?L’exemple de la région Auvergne-Rhône-Alpes - Claire Delfosse; Mathilde Ferrand; Geneviève Ganivet; Patrick Grimault (Bulletin de l’Association de Géographes Français)
Concerns about poverty and precariousness phenomena in rural areas are being increasingly recognized ; nevertheless, the heterogeneity among rural areas constitutes an obstacle for taking care of them. And yet, some difficulties are specifically rurality-related matters. Deterioration of travel conditions reinforce the difficulties and limit access to basic human rights. Access to affordable housing and a strong inter-knowledge are additionnal factors compelling us to reconsider the best way to intervene in rural areas. Regarding poverty as well as the complexity of the forms it can take, actions aimed at improving the situation of people in precarious situations are diverse and mobilise a wide range of stakeholders in various fields with their very own scope of intervention. In order to adapt more efficiently to the specific features of their regions, stakeholders dealing with these issues are testing more territorialised and collaborative actions, often at the scale of inter-municipal associations. Innovative approaches are emerging. Although some territories and measures embed the fight against poverty within local projects and community development, these actions remain minimal.